Underground Soldier - Skrypuch M. F.; Skrypuch Marsha Forchuk (Toronto New York London Auckland Sydney Mexico City New Delhi Hong Kong Buenos Aires Scholastic Canada Ltd., 2014)
A companion to the award-winning books Stolen Child and Making Bombs for Hitler. Fourteen-year-old Luka works as an Ostarbeiter in Nazi-occupied Eastern Europe, alongside Lida from Making Bombs for Hitler. Desperate to escape the brutal conditions of the labour camp, he manages to get away by hiding in a truck under a pile of dead bodies. Once free, Luka joins a group of Ukrainian resistance fighters. Caught between advancing Nazis in the west and Soviet troops in the east, they mount guerilla raids, help POW escapees, and do all they can to make life hard for the Nazis and Soviets. After the war, Luka must decide whether to follow Lida to Canada or stay in Europe and search for his long-lost mother. Underground Soldier is a companion book to Stolen Child and Making Bombs for Hitler, and a perfect entry point into the series for new readers, as the books can be read in any order.
Keywords: 82-3 (NhUDOVNQ PROZAs